ATIVIDADE ANTI-Candida DE Anacardium occidentale L. in vitro e in vivo - OLIVEIRA, Aluisio da Silva (2022)
Fungal infections caused by Candida spp. increased worldwide, and are related to the high rates of hospitalization and mortality. The treatment of candidiasis includes different types of antifungals, such as Fluconazole and Amphotericin B. However, the increase number of resistant strains motivates the search for new therapeutics. Anacardium occidentale L., a plant species native to Brazil, is popularly used for the treatment of infections and inflammation, for this reason, this species is an interesting target for the bioprospecting of new bioactive compounds. The present study investigated the antifungal effect of the Ethanol Extract of A. occidentale flowers (EAO) against Candida spp, considering the activity against some virulence factors in vitro, and the protective effect in alternative against lethal Candida infection in Tenebrio molitor larvae and mice. The chemical composition of the extract was determined by Mass Spectrometry (MS) with direct melting. Minimum Inibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) determined the antifungal activity. It was also determined the EAO effect on Candida adhesion, biofilm development and the phospholipase and proteinase exoenzymes. The hemolytic activity of EAO was evaluated using sheep red blood cells. T. molitor lethally infected with C. albicans or C. parapsilosis received EAO (intracoelomic, 5mg/Kg) to evaluate the extract effecton survival. Swiss female mice, 2 months of age, were immunosuppressed with Cyclophosphamide (50mg/kg, via intraperitoneal), 48h before infection. Those animals were divided into three groups (N=5/group): Control, received saline groups; ANFO B, treated with Amphotericin B (0.6 mg/kg); EAO, treated with the extract (5 mg/Kg). After 24 hours the animals were euthanized to evaluate the effect of EAO on fungal burden, cellularity and cytokine production.. The major compounds found the EAO included; heptagalloylglucopyranoside, trigalloylglucopyranoside, anacardic acid and galoilquinic were identified. EAO showed anti-Candida activity, for reference strains and clinical isolates of C.albicans and C. parapsilosis. The MIC values ranged from 1.97 to 3.13 mg/mL for the reference strains and 1.97 to 6.25 mg/mL for the clinical strains. The extract inhibited the growth of all fungal species tested, indicating fungicidal and/or fungistatic action according to the MIC/CFM ratio. In addition, EAO inhibited adhesion and biofilm in all tested species and interfered with the production of the proteinase and phospholipase exoenzymes. EAO increased the lifespan of T. molitor larvae and mouse and increased IL-6 and decrease TNF-levels in serum of infected mice. In conclusion, treatment with EAO increased the survival of T. molitor larvae and mice showed activity certainly related to a broad spectrum of antiCandida action, since the extract was also able to inhibit the growth of C. albicans and C. parapsilosis, the adhesion, biofilm and exoenzymes actions. Those activities may be due to the presence of compounds in this extract.